IIRR: Assisting with teaching and learning - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Suppose you are interested in learning how to grow a lot of food on a little land, by the use of organic fertilizers, local plants and natural pesticides, or how appropriate technologies can offer cheap alternatives to poor farmers. In which case,...